Measuring physiological and pathological femoral anteversion using a biplanar low-dose X-ray system: validity, reliability, and discriminative ability in cerebral palsy. - Thépaut, Matthias; Brochard, Sylvain; Leboucher, Julien; Lempereur, Mathieu; Stindel, Eric; Tissot, Valentin; Borotikar, Bhushan; Thépaut, Matthias; Borotikar, Bhushan S (Skeletal Radiology, 2016)
Objective: The aims of this study were to evaluate the concurrent validity and reliability of a low-dose biplanar X-ray system (Ld-BPR) for the measurement of femoral anteversion (FA) by comparing Ld-BPR-based three-dimensional measures with CT-scan-based measures and to assess the discriminative ability of this method in children with cerebral palsy.Materials and Methods: Fifty dry femora were scanned using both a CT scan and the Ld-BPR system. Ten femora were artificially modified to mimic a range of anteversion from -30° to +60° and scanned by both modalities. FA was quantified using the images from both modalities and statistically compared for concurrent validity. Intra- and inter-observer reliability of the Ld-BPR system was also determined. Further, Ld-BPR data from 16 hemiplegic and 22 diplegic children were analyzed for its discriminative ability.Results: The concurrent validity between the Ld-BPR and CT-scan measures was excellent (R (2) = 0.83-0.84) and no significant differences were found. The intra- and inter-trial reliability were excellent (ICCs = 0.98 and 0.97) with limits of agreement of (-2.28°; +2.65°) and (-2.76°; +3.38°) respectively. Further, no significant effects of angle or method were found in the sample of modified femora. Ld-BPR measures for FA were significantly different between healthy and impaired femora.Conclusions: The excellent concurrent validity with the CT scan modality, the excellent reliability, and the ability to discriminate pathological conditions evaluated by this study make this radiological method suitable for a validated use across hospitals and research institutes.